(untitled) (Nepalese Journal of Radiology, 2022)
Computerized Tomography(CT) scan plays an important role in the diagnosis and treatment of sinus and skull base lesions. The CT image distinctly provides detail of bony anatomy, anatomical variation, and the extent of diseases, and differentiates between inflammatory, benign, and malignant sinus and skull base pathology.1 It is an important aspect of imaging that helps not only the diagnostic role but also rules out other sinus pathology and helps in designing the surgical plan by 3D-MPR and 3D VRT CT scan. Osteomas of the paranasal sinuses are slow-growing, benign tumours most frequently found in the frontal sinus with an incidence that varies from 47% to 80% of the cases. It can be associated with sinusitis. The patient may present either with a unilateral headache that is difficult to differentiate from a migraine or often no symptoms which are diagnosed by chance during a radiological examination. Here we present a case of a 42-year female present with left frontal headache and facial fullness treated with endoscopic and open approaches which were designed by CT paranasal sinus 3-D multiplanar reconstruction(3D-MPR) and from 3-D MPR and volume rendering technique(3D VRT).